(untitled) (UNIZIK Journal of STM Education, 2025)
This study investigated the perceptions of undergraduate science students regarding the use of artificial intelligence in the teaching of mathematics. The targeted population comprised 137 students( 42 male students and 95 female students) in the school of sciences,Nwafor Orizu College of Education, Nsugbe, Anambra State in 2024/2025 academic year .The sample represents the entire poulation of 137 students(comprises of 46 Biology ,18 Chemistry,10Mathematics ,4 Physics ,59 Computer Science) ,who enrolled for the Elementary Mathematics 1( MTH101)lesson using census sampling method because .This is becauseThe instrument for data collection was a 30 item 4 -point scale questionnaire classified into five thematic category named as Artificial Intelligence Perception Questionnaire(AIPQ). The data obtained was analyzed using mean, standard deviation and t-test statistics. From the findings of the study, it was determined that artificial intelligence perceptions of the students of the Computer Science , Mathematics and Physics students perception were higher than the students of the Biology and chemistry departments. Also the negative perceptions of all sample groups about artificial intelligence concept are more significant than positive perceptions.Based on the findings,it was recommended among others that the Nigeria curriculum should incorporate AI literacy, helping students understand the strengths, limitations, and proper applications of AI in mathematical problem-solving.